Overcoming the Initial Illegitimacy of Ideas - Eicher, Stephan (Corporate Underground, 2022)
This chapter presents how bootleggers uncover their underground projects to their organizations and overcome the initial illegitimacy of their ideas. This study seems to be the first attempt to link bootlegging research with legitimacy research to explain this endeavor.We find that bootleggers just as other innovators need to win legitimacy for their projects. To overcome initial illegitimacy, we find that they follow several known but also several new patterns. Consequently, this chapter expands the knowledge on legitimacy seeking behavior of innovators and closes the research gap of how bootleggers successfully uncover their clandestine projects. Our collection of cases furthermore highlights that managers should listen carefully when being confronted with such projects. Innovations that may appear illegitimate at first can turn into important assets for their firms.
CRIS-Team Scopus Importer:2024-12-16